The Effect Of Dividend And Profitability Policy On Company Value At PT. Nippon Indosari Corpindo Tbk 2015-2024 Period - Ayu, Ajeng Fatma; Nurcahayati, Siti (Fin Sinergy: Jurnal Manajemen Keuangan, 2025)
This study aims to analyze the effect of Dividend Payout Ratio and Profitability (Return on Equity) on Company Value (Price to Book Value) at PT Nippon Indosari Corpindo Tbk for the period 2015-2024. The method used is quantitative descriptive with secondary data from the company's annual financial statements. Data analysis was carried out using SPSS version 29, including descriptive statistical tests, classical assumption tests, multiple linear regression analysis, hypothesis tests, and coefficient of determination tests. The results show that dividend policy has a negative and significant effect on company value, with t count > t table or -2.795 > 2.365 and a significance value of 0.027 < 0.05, while profitability has a positive and significant effect on company value, with t count > t table or 4.647 > 2.365 and a significance value of 0.002 < 0.05. Simultaneously, both variables have a significant effect on company value with Fcount > Ftable or 14.935 > 4.74, and a significance value of 0.003 < 0.05. The Adjusted R Square Determination Coefficient shows a 75.6% contribution of both variables to company value, while 24.4% is influenced by other factors not examined.